Ventilation System Design and the Coronavirus (COVID-19) - Afshari, Alireza; Hultmark, Göran; Nielsen, Peter V.; Maccarini, Alessandro (Frontiers in Built Environment, 2021)
Most new office buildings in Nordic countries are equipped with balanced mechanical ventilation systems. The purpose of ventilation in office buildings is to provide thermal control by supplying cold or warm air for adequate indoor air quality. However, the role of ventilation in preventing virus transmission and maintaining a sufficient fresh air supply to obtain a low virus level through dilution is not currently well defined. Ventilation in office buildings is expected to contribute to preventing the spread of contaminants and provide comfort for occupants. The study reveals differences between risk areas for spreading airborne contaminants in office buildings in northern Europe, including Denmark, Norway and Sweden. The differences in the spread depends on different ventilation designs used in different countries.